ANALISIS SISTEM TATANIAGA BERAS SIAM BANJAR DI KECAMATAN SUNGAI TABUK KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Fitri Mahyudi; Husinsyah; Yarna Hasiani (Fakultas Pertanian UVAYA Banjarmasin, 2025)
Rice from the Siam Banjar cultivar has become a very salable commodity in the South Kalimantan. The high interest in consumption of Siam Banjar rice makes the price of this rice quite high at the retailer level, but the selling price of dry milled unhulled rice and rice is quite cheap at the farmer level. The purpose of this study was to map the Siam Banjar rice trading system so that it became a recommendation for farmers in distributing rice and setting prices so that they would not suffer losses due to high capital of agricultural production facilities. Observational indicators were analysis of institutions and functions of trading system, channel of trade, analysis of trading margin, farmer's share, profit, marketing costs, R/C ratio and analysis of market structure in three Village this’s Pematang Panjang, Gudang Hirang, and Abumbun Jaya, on Sungai Tabuk District, Banjar in October – December 2025 with snowball sampling method. The results of the analysis show that the channel system of trade from farmers to Gapoktan to rice mills to retailers to final consumers is the most profitable channel, but capital from Gapoktan and rice mills is a limiting factor in accommodating the value of profits that should be felt by farmers.